1985
DOI: 10.1021/jf00063a044
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of captan on apples, grapes, and pears in Ontario, Canada, 1981-1983

Abstract: Blocks of apples, grapes, and pears were treated with captan at 1.7,2.8, or 3.4 kg ha"1 for 1-15 applications. Captan residues were measured over a 14-day period following the last application. Residues declined significantly in seven of nine experiments. Correlations between rainfall and captan residues were observed in five experiments. No correlations were observed in four experiments in which little or no rain fell in the first 7 days. In four of the trials the captan residues immediately following the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
3

Year Published

1988
1988
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 0 publications
4
18
3
Order By: Relevance
“…As reported previously (Smith and MacHardy 1984;Frank et al 1985;1987;Northover et al 1986), there was a significant loss of captan due to wash-off by rain. The relationships between the loss and the amount of rainfall varied greatly between experiments and fields.…”
Section: Model Parameters For Captansupporting
confidence: 80%
See 3 more Smart Citations
“…As reported previously (Smith and MacHardy 1984;Frank et al 1985;1987;Northover et al 1986), there was a significant loss of captan due to wash-off by rain. The relationships between the loss and the amount of rainfall varied greatly between experiments and fields.…”
Section: Model Parameters For Captansupporting
confidence: 80%
“…Several previous studies reported that there was no appreciable loss of captan on tomato fruit (Frank et al 1987), apple and grape (Frank et al 1985), and cherry and peach (Northover et al 1986) under dry conditions. However, large loss of captan was shown under dry conditions in another field study (Smith and MacHardy 1984), which may have resulted from heavy dew.…”
Section: Model Parameters For Captanmentioning
confidence: 89%
See 2 more Smart Citations
“…Although iprodione has been used extensively in the production of grapes to control fruit rot, some resistance to this product has been reported and captan has been identified as the replacement in Canadian fruit (Frank et al 1985). Captan is known to degrade completely during the wine production process, while iprodione can be detected in wine (Cabras and Conte 2001).…”
Section: Resultsmentioning
confidence: 99%